2021
DOI: 10.1186/s13020-020-00413-y
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological activities and mechanisms of action of Pogostemon cablin Benth: a review

Abstract: Patchouli (“Guanghuoxiang”) or scientifically known as Pogostemon cablin Benth, belonging to the family Lamiaceae, has been used in traditional Chinse medicine (TCM) since the time of the Eastern Han dynasty. In TCM theory, patchouli can treat colds, nausea, fever, headache, and diarrhea. Various bioactive compounds have been identified in patchouli, including terpenoids, phytosterols, flavonoids, organic acids, lignins, glycosides, alcohols, pyrone, and aldehydes. Among the numerous compounds, patchouli alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 124 publications
(143 reference statements)
0
41
0
Order By: Relevance
“…Moreover, previous studies showed that A. paniculata methanol extract could cure mild to moderately active ulcerative colitis (Nyeem et al 2017). However, P. cablin is widely used in gastrointestinal disease and exterior syndromes, confirmed by both in vitro and in vivo studies (Chen et al 2013;Mishra et al 2013;Junren et al 2021). To exploit this, traditional medicine that adequately fits modern drugs is used to treat specific ailments known as gastrointestinal and OB-Gynecology illnesses (Table 4).…”
Section: Fidelity Levelmentioning
confidence: 95%
“…Moreover, previous studies showed that A. paniculata methanol extract could cure mild to moderately active ulcerative colitis (Nyeem et al 2017). However, P. cablin is widely used in gastrointestinal disease and exterior syndromes, confirmed by both in vitro and in vivo studies (Chen et al 2013;Mishra et al 2013;Junren et al 2021). To exploit this, traditional medicine that adequately fits modern drugs is used to treat specific ailments known as gastrointestinal and OB-Gynecology illnesses (Table 4).…”
Section: Fidelity Levelmentioning
confidence: 95%
“…The metabolism of PA in gastric acid provides a new direction for us. PA will be transformed into β-patchoulene (β-PAE) in acid which suggested more powerful anti-inflammatory activity than PA (Junren et al, 2021). Studies have reported the use of β-cyclodextrin to encapsulate PA, improving its stability in vivo (Xu et al, 2017a), and lactoferrin has been used to deliver PA to inflammatory colonic macrophages that express LRP1, the receptor of lactoferrin (Zhao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Normally, NF-κB associates with its inhibitor IκB in the cytoplasm and exists in an inactive state, but the inflammatory response induces dissociation of the NF-κB dimer, resulting in the nuclear translocation of p65. Therefore, the excessive activation of OCs by inflammation is also closely related to osteoporosis (Napetschnig and Wu 2013;Junren et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Patchouli, also known as Pogostemon cablin Benth, is a Lamiaceae family flowering plant used in TCM formulations since the Han dynasty to treat colds, diarrhea, fever, headache, and nausea. The patchouli herb contains several bioactive compounds, including terpenoids and others, the most important of which are β-patchoulene, patchoulene epoxide, and patchouli alcohol, all of which have anti-peptic ulcer, anti-inflammatory, anti-microbial, anti-tumor, anti-diabetic, anti-oxidative, anti-hypertensive, and immune regulatory properties [132] . Patchouli extracts have been shown to protect against bacterial infections [133] , other than H. pylori -induced gastric ulcers, and suppress adipogenesis and fat accumulation in adipose tissues [132] .…”
Section: Application and Efficacy Of Single Prescriptions Used In Tcm Formulasmentioning
confidence: 99%